2020
DOI: 10.3390/agriculture10110511
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Risks of Farmers in the Olive Grove (Jaén-Spain)

Abstract: Spain is the largest producer of olive oil in the world and, consequently, it has the world’s largest olive-growing area. Workers are highly exposed to musculoskeletal risks due to the manual nature of most of the tasks they perform. The objective of this study is to assess the musculoskeletal risks faced by olive workers in the province of Jaén (Spain) using the Standardized Nordic Questionnaire. This consists of 28 questions and analyzes the wrists/hands, elbows, shoulders, neck, back, hip, ankles, and knees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…16,17 Furthermore, many WRMSDs studies have also been conducted among agricultural workers which included plantation workers and farmers as well as gardeners. [18][19][20][21][22][23] The most prevalent WRMSDs were reported in the lower back region (53.3-86.5%) followed by the neck (23.9-85.9%) and shoulder regions (21.6-80.9%). [18][19][20][21][22][23] Therefore, ergonomic risk assessment is deemed necessary among landscape workers who are working in potentially hazardous environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Furthermore, many WRMSDs studies have also been conducted among agricultural workers which included plantation workers and farmers as well as gardeners. [18][19][20][21][22][23] The most prevalent WRMSDs were reported in the lower back region (53.3-86.5%) followed by the neck (23.9-85.9%) and shoulder regions (21.6-80.9%). [18][19][20][21][22][23] Therefore, ergonomic risk assessment is deemed necessary among landscape workers who are working in potentially hazardous environments.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] The most prevalent WRMSDs were reported in the lower back region (53.3-86.5%) followed by the neck (23.9-85.9%) and shoulder regions (21.6-80.9%). [18][19][20][21][22][23] Therefore, ergonomic risk assessment is deemed necessary among landscape workers who are working in potentially hazardous environments. Furthermore, it is also in accordance with the Occupational, Safety and Health Act (OSHA), which highlighted the responsibility of employers in providing and maintaining the safety, health, and welfare of workers in the working environment.…”
Section: Introductionmentioning
confidence: 99%
“…10 The most prevalent MSD symptoms were back and knee pains, which is consistent with similar studies. 18,20,21 The results also indicated lower limb MSDs, while Kim et al reported at least one MSD in the upper limbs. 22 One probable reason for the difference in the results is the type of work done by the participants in this study and many similar ones, the farmers worked in farms and orchards, while in the studies with inconsistent results, the participants were only orchardists.…”
Section: Discussionmentioning
confidence: 71%
“…Alternating between subtasks, such as cleaning the greenhouse or preparing the crop. Some tasks could be mechanized (ILO, 2011[ 29 ]) while seeking a balance with agricultural sustainability (Barneo-Alcántara et al, 2020[ 4 ]). Encouraging the taking of breaks during each subtask (ILO, 2011[ 29 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Some tasks could be mechanized (ILO, 2011[ 29 ]) while seeking a balance with agricultural sustainability (Barneo-Alcántara et al, 2020[ 4 ]).…”
Section: Discussionmentioning
confidence: 99%